What Is the Clinical Relevance of TNF Inhibitor Immunogenicity in the Management of Patients With Rheumatoid Arthritis? - Mehta, Puja; Manson, Jessica J. (Frontiers in Immunology, 2020)
Tumour necrosis factor-α inhibitors (TNFis) have revolutionised the management of rheumatoid arthritis (RA), however despite considerable progress, only a small proportion of patients maintain long-term clinical response. Selection of, and switching between, biologics is mainly empirical, experiential and not evidence-based. Most biopharmaceutical proteins (BP) can induce an immune response against the foreign protein component. Immunogenicity and the development of anti-drug antibodies (ADAs) is considered one of the main reasons for loss of therapeutic efficacy (secondary failure). ADAs may neutralise and/or promote clearance of circulating BP with resultant low serum drug levels, loss of clinical response, poor drug survival and adverse events, such as infusion reactions. ADA identification is technically difficult and not standardised, making interpretation of immunogenicity data from published clinical studies challenging. Trough TNFi drug levels correlate with clinical outcomes, exhibiting a ‘concentration-response’ relationship. Measurement of ADA and drug levels may improve patient care and improve cost-effectiveness of BP use. However, in the absence of clinically-validated, reliable assays and consensus guidelines, therapeutic drug monitoring (TDM) and immunogenicity testing have not been widely adopted in routine clinical practice in Rheumatology. Here we discuss the utility and relevance of TDM and immunogenicity testing of TNFis in RA (focusing on the most widely used TNFis globally, with the most available data, i.e. infliximab, adalimumab and etanercept), the limitations of currently available assays and potential future immunopharmacological strategies to personalise disease management.